FOREIGN READING AS AN IMPORTANT COMPONENT INDEPENDENT LEARNING ACTIVITIES OF STUDENTS (Pedagogy of Higher and Secondary Education, 2008)
The article deals with the importance and methods and ways of students' mastering different types of foreign language reading in the process of independent educational activity.